INTERACTIVE LEARNING MULTIMEDIA: ENHANCING VOCABULARY MASTERY FOR JUNIOR HIGH SCHOOL STUDENTS - Wahyu Budiyani; Sujarwo Sujarwo (Jurnal Kependidikan, 2020)
This study was aimed at improving junior high school students’ vocabulary mastery. The subjects of this study were the students grade 7 of junior high school with a total number of 60 students. The method employed in this study was the Research and Development design. The development model used is the ADDIE modification development model. The steps in the ADDIE development consist of five stages; namely analyzing, design, development, implementation, and evaluation. Product trials are carried out in three stages, namely small group trials, operational trials, and large group trials.. The instruments used in development research were observation sheets, interviews, and assessment questionnaires. A t-test was used to analyze the effectiveness of media development. The media then were validated by the media experts, material experts, and teachers. The results shows that the media is feasible with an average score of 4.55. The findings also show that the Interactive Learning Multimedia effectively enhance students’ vocabulary mastery for junior high school students and able to be used as a catalyst or alternative media teaching vocabulary.